2022
DOI: 10.3390/vaccines10081345
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with COVID-19 Vaccines in Health Care Workers and the General Population: A Cross-Sectional Study in Urban Bangkok, Thailand

Abstract: Background: COVID-19 vaccination hesitancy is a global issue. Many people are concerned about experiencing side effects from the vaccine. This study evaluated satisfaction with the COVID-19 vaccine in the general population (GP) and healthcare workers (HCWs) in Bangkok, Thailand. Methods: A cross-sectional online survey was distributed from September-December 2021. Independent sample t-tests were used to compare GP and HCW participants’ total vaccine satisfaction scores as well as their satisfaction with varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In addition, only 28.8% of the population in Bangkok received the booster dose from September to December 2021. During the data collection period (March 2022–June 2022), it was found that the uptake rate of COVID-19 booster doses in the Bangkok Metropolitan Region in this study was 2 times higher than the previous report 3 months later [ 46 ] because the risk of transmission and safe activity resumption in the public area were elicited by taking COVID-19 booster vaccinations during the rise of the Omicron variant [ 33 ]. The policy of COVID-19 booster doses among the entire population was strongly supported by the Thai government [ 25 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, only 28.8% of the population in Bangkok received the booster dose from September to December 2021. During the data collection period (March 2022–June 2022), it was found that the uptake rate of COVID-19 booster doses in the Bangkok Metropolitan Region in this study was 2 times higher than the previous report 3 months later [ 46 ] because the risk of transmission and safe activity resumption in the public area were elicited by taking COVID-19 booster vaccinations during the rise of the Omicron variant [ 33 ]. The policy of COVID-19 booster doses among the entire population was strongly supported by the Thai government [ 25 ].…”
Section: Discussionmentioning
confidence: 91%
“…To sum up, good knowledge of booster dose vaccination and a good attitude with trust were found to be strong predictors of COVID-19 booster dose vaccination among populations in the areas with a high risk of environmental exposure. Therefore, an educational campaign on the effectiveness and safety of vaccinations was still demanded to expand public attitudes toward COVID-19 booster dose vaccinations [ 46 ] and was urgently needed in Thailand [ 47 ]. From this result, the findings imply that the potential risk of transmission with the pollution reduction in cities can be deduced for the incident rate of future COVID-19 pandemics.…”
Section: Discussionmentioning
confidence: 99%
“…The VE of these vaccines in HCWs ranged from 66% to 99%. Many factors were documented to increase the vaccine efficacy: 1. the administration of a second and booster dose significantly increased vaccine efficacy [ 16 , 17 ]; 2. the interval time increased between vaccine doses [ 18 ]; 3. Moderna had the highest documented vaccine effectiveness [ 19 ]; 4.…”
Section: Resultsmentioning
confidence: 99%